Fibres: Polymer Brushes Tethered ZnO Crystal on Cotton Fiber and the Application on Durable and Washable UV Protective Clothing (Adv. Mater. Interfaces 14/2019). Issue 14 (23rd July 2019) - Wang, Xi; Chen, Xiaogang; Cowling, Stephen; Wang, Libo; Liu, Xuqing
Abstract : Grafted polymer brushes are used as platforms for in‐situ growth of zinc oxide (ZnO) nanocrystals on cotton fibres by electroless deposition. The functional ZnO nanocrystals are grown not only on the surface of the fibers but also inside of the hollow cotton fibers, but with a different morphology. In this case, the ultraviolet (UV) blocking fabric shows good antifriction capability and durability. More details can be found in article number1900564 by Xi Wang, Xuqing Liu, and co‐workers.